Planos municipais de ação para a população idosa em municípios do Paraná, certificados como cidades amigas das pessoas idosas: um olhar para a década do envelhecimento saudável nas Américas 2021-2030 - Nespolo, Juliana Mara (2023)
The population aging phenomenon is a structural fact, present in contemporary societies and with the increase in life expectancy, the increase in the number of elderly people in the world is significant, representing challenges of a social, political and economic nature, regarding to the care for the elderly population at local, national and global levels. With this, international organizations such as the UN and WHO seek to alert countries about the challenges of population aging and the need for cities to prepare, adapting their structures and services to be able to better serve the elderly and promote active, healthy and quality aging. It is in this context that the WHO Age-Friendly Cities and Communities Program, the Global Network of Age-Friendly Cities and Communities and the Decade of Healthy Aging in the Americas 2021/2030 emerged. The objective of the research was to analyze how the Municipal Action Plans for the Elderly Population of towns in Paraná, certified as age-friendly cities by the WHO, add guiding principles of the Decade of Healthy Aging in the Americas 2021-2030 and how these actions can reflect on local development. This is a descriptive and exploratory study, with field research, using procedures such as questionnaires and an interview with a focus group in online format, bibliographical and documental. The research site was the towns of Pato Branco, Dois Vizinhos and Santo Antônio do Sudoeste. For the analysis of the collected data ita was used Minayo's dialectical hermeneutic method, which through this, it was possible to meet the objective of the research. Thus, it is concluded that the Global Network of Cities and Communities Friendly to the Elderly Person is an important initiative that responds to the rapid aging of the population; that the Municipal Action Plans for the Population are valuable instruments for planning and managing public policies; that the work of the Federal Technological University of Paraná – UTFPR was fundamental in the international certification of towns in Paraná as friendly to the elderly; It is known that the Municipal Action Plans for the Elderly Population of the municipalities of Dois Vizinhos, Pato Branco and Santo Antônio do Sudoeste add guiding principles of the Decade of Healthy Aging in the Americas 2021-2030 and the actions foreseen in them, by promoting active and healthy aging , reflect on improvements in the quality of life of the elderly and, consequently, on local development.